Virtual and hybrid event: how Indonesian event organizers adapt during the COVID-19 pandemic - Rakhman Priyatmoko; Tatang Rusata; Priya Falaha Muttaqien; Muhammad Iqbal Rosyidi; Chamma Fitri Putri Pradjwalita (International Journal of Applied Sciences in Tourism and Events, 2022)
This study suggests how adaptive event organizers should be toward virtual and hybrid events, explore the constraints, and recommend policies to support virtual and hybrid events in Indonesia. It uses a quantitative descriptive method, and data are collected through an online survey using the Survey Monkey application. The survey was conducted from August to September 2021, involving 170 event organizer managers. The result shows that they mostly earn income from management fees during the pandemic. Event organizers also take several ways to increase engagement in virtual events, such as combining internal and external resources to serve personnel and technical equipment and to keep the events productive. Policy support through capacity building in some aspects is highly recommended to increase the managerial skills of event organizers to produce higher quality outputs of the event. The suggested training materials cover how to monetize virtual events, how to improve skills in the technological aspects, and how to increase engagement for participants. This research provides an overview of virtual and hybrid events in Indonesia so that the government can take the necessary policies in creating quality events, especially during the pandemic.